PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT MELALUI MANIPULASI AKTIVITAS RIIL - Yudhitya Dian Pratiwi; Wahyu Meiranto (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of the application of corporate governance on earnings management is detected through the manipulation of real activities through the provision. Variables tested in this study, namely board size, number of board meetings, independent board composition, audit committee size, the number of audit committee meetings, the competence of the audit committee, audit quality, firm size, and earnings management through real activities.The research was conducted by analyzing the influence menngenai application of corporate governance and earnings management through real activities manipulation during the years 2009-2011 at the companies listed on the Stock Exchange and analyzed by multiple regression analysis. Then the proxy-proxy corporate governance partially analyzed the effects on earnings management through real activities manipulation.The results indicate that board size and competence of the audit committee significant influence. While the number of board meetings, competence independent board, audit committee size, the number of audit committee meetings, and audit quality does not significantly affect earnings management through real activities manipulation.